2004
DOI: 10.1093/mutage/geh029
|View full text |Cite
|
Sign up to set email alerts
|

The use of EBV-transformed cell lines of breast cancer patients to measure chromosomal radiosensitivity

Abstract: To investigate the chromosomal radiosensitivity of lymphocytes in cancer patients the micronucleus (MN) assay is often used and performed on freshly drawn peripheral blood lymphocytes. The use of Epstein-Barr virus (EBV)-transformed lymphoblastoid cell lines may have a lot of advantages (e.g. large pool of cells) compared with fresh blood samples. In this study we have investigated whether the response of EBV-transformed lymphoblastoid cell lines to irradiation in the G1/S/G2 phases of the cell cycle is the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…b Multivariate linear regression included terms for age (years), BMI (kg m À2 ), current smoker (yes/no), alcohol intake (total drinks of per day), physical activity (total hours per week), and total daily caloric intake (kcal). radiation when compared to peripheral blood lymphocytes (Baeyens et al, 2004). Strengths of our study include the evaluation of multiple endpoints (before and after exposure to g-irradiation), a relatively large sample of carriers, the use of controls who were from a family with a previously identified mutation, and employing a single technician who was blinded to the mutation status of the samples.…”
Section: Discussionmentioning
confidence: 99%
“…b Multivariate linear regression included terms for age (years), BMI (kg m À2 ), current smoker (yes/no), alcohol intake (total drinks of per day), physical activity (total hours per week), and total daily caloric intake (kcal). radiation when compared to peripheral blood lymphocytes (Baeyens et al, 2004). Strengths of our study include the evaluation of multiple endpoints (before and after exposure to g-irradiation), a relatively large sample of carriers, the use of controls who were from a family with a previously identified mutation, and employing a single technician who was blinded to the mutation status of the samples.…”
Section: Discussionmentioning
confidence: 99%
“…However, these assays require cell activation or transformation, and the time required to produce the data varied from days in case of cytogenetic tests in lymphocytes (dysenteric chromosomes, micronuclei, translocations, DNA fragments) to months for clonogenic survival. It has been reported that transformation itself may disrupt the radiosensitivity of normal cells [111; 112]. Geara and Peters [109; 113] reported lack of correlation between radiosensitivity of transformed lymphocytes and primary fibroblasts cultured from skin biopsy samples.…”
Section: Individual Radiosensitivitymentioning
confidence: 99%
“…1), heterozygous for the c.190T>C mutation in BRCA1. Immortalization was achieved by exposure of lymphocytes to the supernatants of the B95-8 EBV producer cell line, according to a standard protocol (20). EBV cell lines were used to amplify transcript sequences of the BRCA1 gene by RT-PCR, and for radiosensitivity testing with the cytokinesisblock micronucleus (MN) assay, as previously described (20).…”
Section: Detection Of Brca1 and Brca2 Mutations And Polymorphismsmentioning
confidence: 99%
“…Immortalization was achieved by exposure of lymphocytes to the supernatants of the B95-8 EBV producer cell line, according to a standard protocol (20). EBV cell lines were used to amplify transcript sequences of the BRCA1 gene by RT-PCR, and for radiosensitivity testing with the cytokinesisblock micronucleus (MN) assay, as previously described (20). The EBV cell lines were maintained in RPMI-1640 medium supplemented with 10% fetal bovine serum, 2 mM L-glutamine, 100 U/ml penicillin, 0.1 mg/ml streptomycin with 10% FBS and cultured at 37˚C, 5% CO 2 , in a humidified incubator.…”
Section: Detection Of Brca1 and Brca2 Mutations And Polymorphismsmentioning
confidence: 99%